PERENCANAAN SISTEM DRAINASE SEPANJANG JALAN RAYA MAYONG – BAKALAN KABUPATEN JEPARA - Huda, Miftakhul (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2021)
The problem of annual periodic flooding that occurs in Mayong – Bakalan, Jepara Regency disrupts the flow of local traffic so that it hampers the speed of vehicles. Then this study aims to determine the ability of drainage in draining wastewater discharge, to determine the capacity of drainage, and provide solutions to these problems. This study previously reviewed the condition of the existing canal first, by collecting primary and secondary data and then analyzed it using HEC – RAS 5.0.7 software. With hydrological analysis using the HEC-RAS 5.0.7 software, it will be easier to plan a drainage again with a simulation of channel conditions. In the calculation analysis using the Pearson III log distribution because the value of Cs < 1 from this method, the rainfall for 2 years = 291,071 mm, 5 years = 254,813 mm, 10 years = 394.457 mm, 25 years = 443.608 mm. From the results of this study, the planned flood discharge for Q 2019 is 57.84 m3/s, Q 2021 is 64.10 m3/s, Q 2024 is 69.52 m3/s, and Q 2029 is 74.79 m3/s. while the HEC – RAS 5.07 software produces an average channel discharge of Q 2.44 m3/s where Q Discharge > Q Channel, it is stated that the Q channel does not meet the requirements to drain flood discharge so that runoff occurs. For this reason, it is planned for a 10-year scale using a U-ditch with dimensions b = 1 m and h = 1 m with a manning roughness of 0.014 and a channel slope of 2.75%, from the results of the analysis using HEC-RAS 5.0.7 software so that it meets the requirements and safe to accommodate flood discharge.